Comparison of Multiplex Real-Time PCR and PCR-Reverse Blot Hybridization Assays for the Direct and Rapid Detection of Porcine Circovirus Type 2 Genotypes - Wang, Hye-young; Song, Joong Ki; Shin, Seongho; Kim, Hyunil (Frontiers in Veterinary Science, 2020)
Porcine circovirus type 2 (PCV2), the causative agent of porcine circovirus-associated diseases (PCVAD), poses a serious economic threat for the swine industry. Currently, PCV2 is classified into five major genotypes: PCV2a, PCV2b, PCV2c, PCV2d, and PCV2e. The aim of this study is to evaluate the performance of two commercially available methods, multiplex real-time PCR assay and PCR-reverse blot hybridization assay (REBA), for the rapid detection of PCV2 and direct identification of PCV2 genotypes from clinical samples as well as to compare the results with that of sequence analysis. Molecular diagnostic methods were used to evaluate a total of 180 samples, including tissues and blood samples from pigs that were suspected of PCVAD infection. The results of this study showed that the detection rate for positive PCV2 was 48.3% (n=87) in both multiplex real-time PCR and PCR-REBA methods. Using sequence analysis, which is the gold standard, and multiplex real time PCR assay, the sensitivity, specificity, positive predictive value, and negative predictive value of PCV2 genotyping were found to be 97.1% (n=67, 95% CI 0.894-0.998, p<0.001), 100% (n=93, 95% CI 0.966-1.000, p<0.001), 100% (95% CI 0.953-1.000, p<0.001), 97.9% (95% CI 0.921-0.998, p<0.001), respectively. The results of PCR-REBA were found to be consistent with those of sequence analysis for all the samples and showed good agreement (κ=1). The most prevalent genotypes detected in this study were PCV2d (n=53, 60.9%), followed by PCV2a (n=17, 19.5%), PCV2b (n=14, 16.1%), and PCV2a/b co-infection (n=3, 3.5%). Both the methods required approximately 3 hours for completion. Therefore, we conclude that two molecular methods are rapid and reliable for the characterization of the causative pathogen with PCV2 genotypes.